Tourism as the Priority for the Economic Development of Modern Georgia - Kotulewicz, Karolina; Kozłowska, Małgorzata (Central and Eastern European Economic Review, 2016)
Georgia has taken a growing interest in reviving and developing tourism since the late 1990s. The country’s considerable tourist assets make this a valid choice of direction for the country’s economic growth. The paper aims to show the role and significance of tourism in contemporary Georgia. The authorities, who also noted the sector’s importance as a factor of political and international integration, have regarded its development as a main pathway for the state’s economic growth since 2000. It can be seen in the performance of the sector, which has been making a considerable contribution to Georgia’s GDP since the beginning of the century, that the strategy has been successful.